Setting a good example? Examining sibling spillovers in education achievement using a regression discontinuity design - Krzysztof Karbownik; Umut Özek (Center for Economic Studies and ifo Institute (CESifo), 2019)
We identify externalities in human capital production function arising from sibling spillovers. Using regression discontinuity design generated by school-entry cutoffs and school records from one district in Florida, we find positive spillover effects from an older to a younger child in less affluent families and negative spillover effects from a younger to an older child in more affluent families. These results are consistent with direct spillovers dominating in economically disadvantaged families and with parental reinforcement in more affluent families.
Keywords: D13; I20; J13; 330; sibling spillovers; household dynamics; school starting age; regression discontinuity